Kemandirian Pelaku Usaha Mikro Kecil Menengah Toko Kelontong dalam Meningkatkan Ekonomi Keluarga di Kelurahan Balaroa Kecamatan Palu Barat Kota Palu - Hidayat, Rahmat; Samsinas, Samsinas; Abu, Ardillah; Arman, Muhammad (Journal of Islamic Community and Development, 2026)
This study discusses the independence of Micro, Small, and Medium Enterprises (MSMEs) grocery store owners in improving family economic conditions in Balaroa Village, West Palu District, Palu City. The study aims to analyze the level of financial independence of MSME actors in managing their businesses and fulfilling family economic needs. The method used is qualitative research with data collection techniques through observation, interviews, and documentation. Data were analyzed interactively through data reduction, presentation, and verification, and their validity was tested using source, technique, and time triangulation. The results show that the independence of business owners has a significant effect on improving family economic welfare. This independence is reflected in the ability to manage business capital separately from personal needs, organize stock and receivables properly, and build customer loyalty through good communication. The improvement in family welfare is indicated by increased assets, house renovations, vehicle ownership, and the ability to send children to higher levels of education. This study concludes that strong motivation and functional social networks are important factors in supporting the independence of grocery store MSMEs as a reinforcement of household economic stability.